Implementing area-based management of vulnerable marine ecosystems in areas beyond national jurisdiction: A South Pacific case study - Ashley A. Rowden; Fabrice Stephenson; Martin Cryer; Carolyn J. Lundquist; Owen F. Anderson; Matthew Bennion; Andrew Biggerstaff; Tiffany Bock; Tom Brough; Lee Georgeson; Alexandra Macdonald; Marco Milardi; et al. (Ocean & Coastal Management, 2026)

Correction to: Potential future climate-induced shifts in marine fish larvae and harvested fish communities in the subtropical southwestern Atlantic Ocean - Micheli D. P. Costa; Kerrie A. Wilson; Philip J. Dyer; Roland Pitcher; José H. Muelbert; Anthony J. Richardson (Climatic Change, 2021)

Potential future climate-induced shifts in marine fish larvae and harvested fish communities in the subtropical southwestern Atlantic Ocean - Micheli D. P. Costa; Kerrie A. Wilson; Philip J. Dyer; Roland Pitcher; José H. Muelbert; Anthony J. Richardson (Climatic Change, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

A Path to a Sustainable Trawl Fishery in Southeast Asia - Petri Suuronen; C. Roland Pitcher; Robert A. McConnaughey; Michel J. Kaiser; Jan G. Hiddink; Ray Hilborn (Reviews in Fisheries Science & Aquaculture, 2020)

True Size Matters for Conservation: A Robust Method to Determine the Size of Deep-Sea Coral Reefs Shows They Are Typically Small on Seamounts in the Southwest Pacific Ocean - Alan Williams; Franziska Althaus; Mark Green; Kylie Maguire; Candice Untiedt; Nick Mortimer; Chris J. Jackett; Malcolm Clark; Nicholas Bax; Roland Pitcher; Thomas Schlacher (Frontiers in Marine Science, 2020)

Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota - Robert A. McConnaughey; Jan G. Hiddink; Simon Jennings; C. Roland Pitcher; Michel J. Kaiser; Petri Suuronen; Marija Sciberras; Adriaan D. Rijnsdorp; Jeremy S. Collie; Tessa Mazor; Ricardo O Amoroso; Ana M. Parma; et al. (Fish and Fisheries, 2020)
Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studies and a simple conceptual model to evaluate and compare their performance. The risks and benefits of these management measures depend on the extent to which the fishery is already achieving management objectives for target stocks and the characteristics of the management system that is already in place. We offer guidance on identifying best practices for trawl‐fisheries management and show that best practices and their likelihood of reducing trawling impacts depend on local, national and regional management objectives and priorities, societal values and resources for implementation. There is no universal best practice, and multiple management measures and industry actions are required to meet sustainability objectives and improve trade‐offs between food production and environmental protection.

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Biophysical patterns in benthic assemblage composition across contrasting continental margins off New Zealand - Tanya J. Compton; David A. Bowden; C. Roland Pitcher; Judi E. Hewitt; Nick Ellis (Journal of Biogeography, 2013)
Aim To examine whether benthic assemblages are more diverse in a region of high topographic and oceanographic complexity by comparing benthic invertebrate assemblages across continental margins with contrasting environments. Location Challenger Plateau and Chatham Rise, to the west and east of New Zealand, respectively. Methods Benthic faunal data were sourced from extensive seabed surveys in 2007, when both margins were sampled with an epibenthic sled and a towed video system. Three methods were used to investigate benthic assemblages in relation to environmental variables: one based on individual species distribution models ( SDM s) using boosted regression trees analysis ( BRT ), and two community‐based modelling methods using generalized dissimilarity modelling ( GDM ) and gradient forest analysis ( GF ), respectively. Each method was used to model and predict the turnover in assemblages with respect to environment – the ‘biophysical patterns’ – across the study region. Results Across Chatham Rise, a complex oceanographic environment arising from steep gradients in productivity and temperature at the Subtropical Front produced a high diversity of assemblages associated with the sub‐Antarctic water mass, the Subtropical Front, steep‐sloping regions and fast tidal currents. In contrast, Challenger Plateau lies entirely beneath a single (subtropical) water mass, and assemblage diversity was lower, with a distinctive assemblage on the plateau itself and a deep‐water assemblage similar to the northern deep‐water assemblage of Chatham Rise. Across both regions, assemblage turnover was fastest in cold waters, at shallow depths and in deep mixed layers. Main conclusions Benthic assemblages were more varied on Chatham Rise than on Challenger Plateau, supporting the hypothesis that environmentally heterogeneous margins have higher assemblage diversity. Differing assemblages on the northern and southern flanks of Chatham Rise suggest a biogeographical boundary for benthic taxa across the Subtropical Front. These results demonstrate that oceanographically and topographically complex margins have a diverse assemblage structure that should be considered in planning for the sustainable management of diversity.

Gradient forests: calculating importance gradients on physical predictors - Nick Ellis; Stephen J. Smith; C. Roland Pitcher (Ecology, 2012)
In ecological analyses of species and community distributions there is interest in the nature of their responses to environmental gradients and in identifying the most important environmental variables, which may be used for predicting patterns of biodiversity. Methods such as random forests already exist to assess predictor importance for individual species and to indicate where along gradients abundance changes. However, there is a need to extend these methods to whole assemblages, to establish where along the range of these gradients the important compositional changes occur, and to identify any important thresholds or change points. We develop such a method, called “gradient forest,” which is an extension of the random forest approach. By synthesizing the cross‐validated R 2 and accuracy importance measures from univariate random forest analyses across multiple species, sampling devices, and surveys, gradient forest obtains a monotonic function of each predictor that represents the compositional turnover along the gradient of the predictor. When applied to a synthetic data set, the method correctly identified the important predictors and delineated where the compositional change points occurred along these gradients. Application of gradient forest to a real data set from part of the Great Barrier Reef identified mud fraction of the sediment as the most important predictor, with highest compositional turnover occurring at mud fraction values around 25%, and provided similar information for other predictors. Such refined information allows for more accurate capturing of biodiversity patterns for the purposes of bioregionalization, delineation of protected areas, or designing of biodiversity surveys.